2016
DOI: 10.1007/s00404-016-4250-3
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide prevalence of adverse pregnancy outcomes among singleton pregnancies after in vitro fertilization/intracytoplasmic sperm injection: a systematic review and meta-analysis

Abstract: The IVF/ICSI singleton pregnancies are at a higher prevalence of adverse perinatal outcomes compared with those conceived naturally. Important geographical differences were found. Yet, population-wide prospective APO registries covering the entire world population for IVF/ICSI pregnancies are needed to determine the exact perinatal prevalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
108
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(119 citation statements)
references
References 74 publications
6
108
1
4
Order By: Relevance
“…A policy of single-embryo transfer in stimulated cycles becomes more popular and is currently the most effective measure to reduce the incidence of multiple pregnancies [24]. With an increasing implementation of a policy of single-transfer embryo, multiple pregnancies have reduced dramatically [27], but is still an outcome of ART that is undesirable.…”
Section: Discussionmentioning
confidence: 99%
“…A policy of single-embryo transfer in stimulated cycles becomes more popular and is currently the most effective measure to reduce the incidence of multiple pregnancies [24]. With an increasing implementation of a policy of single-transfer embryo, multiple pregnancies have reduced dramatically [27], but is still an outcome of ART that is undesirable.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the rates of stillbirths and neonatal deaths in IVF/ICSI cycles are 0.3%–1.6% and 0.3%–1.1% respectively (Bay, Boie, & Kesmodel, 2019; Magnusson et al, 2018; Qin et al, 2017; Wisborg, Ingerslev, & Henriksen, 2010). In our retrospective study, the rates of stillbirths and neonatal deaths were not significantly different between the two groups and within the range reported in the literatures.…”
Section: Discussionmentioning
confidence: 99%
“…In our selection, the risk estimation was reported as OR for 15 studies [18,29,33,35,[38][39][40][41]52], RR for six studies [19,31,32,36,46,51], SIR for four studies [27,30,43,50], and HR for seven studies [17,44,[47][48][49]53,54]. [27,32,38,40,41], twenty-two studies reported tumors occurring in children aged <15 years [16,18,19,28,[30][31][32][34][35][36][38][39][40][41][42][43]45,[50][51]…”
Section: Study Characteristicsmentioning
confidence: 99%
“…According to the literature [5,54], the risk of pregnancy and neonatal birth adverse outcomes is increased by factors associated with ART procedures, such as the medications used to induce ovulation or to maintain the pregnancy in the early stages, the culture media composition, the length of time in culture, the freezing and thawing of embryos, the potential for polyspermic fertilization, the delayed fertilization of the oocyte, altered hormonal environment at the time of implantation, and the manipulation of gametes and embryos.…”
Section: Soft Tissue and Other Extraosseous Sarcomasmentioning
confidence: 99%